Pre-Colonial Religious Institutions and Development: Evidence through a Military Coup. Issue 2 (11th November 2021) - Malik, Adeel; Mirza, Rinchan Ali
Abstract: This paper offers a novel illustration of the political economy of religion by examining the impact of religious elites on development. We compile a unique database on holy Muslim shrines across Pakistani Punjab and construct a historical panel of literacy spanning over a century (1901–2011). Using the 1977 military takeover as a universal shock that gave control over public goods to politicians, our difference-in-differences analysis shows that areas with a greater concentration of shrines experienced a substantially retarded growth in literacy after the coup. Our results suggest that the increase in average literacy rate would have been higher by 13% in the post-coup period in the absence of shrine influence. We directly address the selection concern that shrines might be situated in areas predisposed to lower literacy expansion. Finally, we argue that the coup devolved control over public goods to local politicians, and shrine elites, being more averse to education since it undermines their power, suppressed its expansion in shrine-dense areas.